Key Competences in the Era of Digitization of Enterprises in the Podkarpackie Voivodship - Buś, Daniel (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
The digitalisation of businesses is one of the most dynamic changes taking place today. On the one hand, it opens up new opportunities in the creation of business models, which may translate into an increase in the competitiveness of individual companies, but on the other hand, it brings with it certain challenges, for example in the form of emerging difficulties in the process of obtaining employees with appropriate competencies. The aim of the article is to identify key competences of employees in the era of digital transformation of enterprises on the example of the Podkarpackie Province. The article uses a triangulation of research methods based on a critical analysis of the literature, qualitative and quantitative research. The analysis shows that the most important key competences include creativity and communicativeness.